Bryophyllum pinnatum and Related Species Used in Anthroposophic Medicine: Constituents, Pharmacological Activities, and Clinical Efficacy - Fürer, Karin; Simões-Wüst, Ana Paula; von Mandach, Ursula; Hamburger, Matthias; Potterat, Olivier (Planta Medica, 2016)
Bryophyllum pinnatum (syn. Kalanchoe pinnata) is a succulent perennial plant native to Madagascar that was introduced in anthroposophic medicine in the early 20th century. In recent years, we conducted a large collaborative project to provide reliable data on the chemical composition, pharmacological properties, and clinical efficacy of Bryophyllum. Here, we comprehensively review the phytochemistry, as well as the pharmacological and clinical data. As to the pharmacology, special emphasis is given to properties related to the use in anthroposophic medicine as a treatment for “hyperactivity diseases”, such as preterm labor, restlessness, and sleep disorders. Studies suggesting that B. pinnatum may become a new treatment option for overactive bladder syndrome are also reviewed. Tolerability is addressed, and toxicological data are discussed in conjunction with the presence of potentially toxic bufadienolides in Bryophyllum species. The few data available on two related species with medicinal uses, Bryophyllum daigremontianum and Bryophyllum delagoense, have also been included. Taken together, current data support the use of B. pinnatum for the mentioned indications, but further studies are needed to fully understand the modes of action, and to identify the pharmacologically active constituents.
Keywords: Bryophyllum pinnatum; Bryophyllum daigremontianum; Bryophyllum delagoense; Crassulaceae; constituents; anthroposophic medicine; pharmacological activities; clinical studies